Mac OS X Snow Leopard for Power Users - Granneman, Scott; Andres, Clay.; Pundick, Douglas; Anglin, Steve; Beckner, Mark.; Buckingham, Ewan.; Cornell, Gary.; Gennick, Jonathan; Hassell, Jonathan; Lowman, Michelle; Moodie, Matthew; Parkes, Duncan; et al. (Berkeley, CA : Apress, 2010)
Mac OS X Snow Leopard for Power Users: Advanced Capabilities and Techniques is for Mac OS X users who want to go beyond the obvious, the standard, and the easy. If want to dig deeper into Mac OS X and maximize your skills and productivity using the world$1 (Bs slickest and most elegant operating system, then this is the book for you. Written by Scott Granneman, an experienced teacher, developer, and consultant, Mac OS X for Power Users helps you push Mac OS X to the max, unveiling advanced techniques and options that you may have not known even existed. Create custom workflows and apps with Automator, run Windows programs and even Windows itself without dual-booting, and sync data on your hard drive, on your phone, and in the cloud$1 (Blearn all of these techniques and more. This is not a book that talks down to you; Mac OS X for Power Users is an essential book for experienced Mac users who are smart enough to know there is more to be known, and are ready to become power users.s
Introduction: Advanced Secrets of Mac OS X -- Maintaining Your Mac -- Expanding Upon the Basic Tools -- Using Safari to Its Fullest -- Stepping Beyond Safari -- Using the Internet to Its Fullest -- Securing Your Mac & Networks -- Backing Up Your Mac -- Manipulating and Sharing Pictures -- Having More Fun With Audio & Video -- Key Utility Tools for Text & Archives -- Digging Deep as an Admin.
Keywords: Computer science; Computer Science; Computer Science, general